Analysis of Potential Human Rights Violations in the Process of Arresting Terrorism Suspects: A Case Study on Lombok Island - Mahmuluddin; Zulkarnain; Wahyudin, Y.A.; Maryanti, Sri (Jurnal Pelita Nusantara, 2024)
In its efforts to address the threat of terrorism, Indonesia faces a significant challenge in balancing national security with the protection of human rights. This study examines the potential for human rights violations during the arrest of suspected terrorists on Lombok Island, a strategic region and international tourism destination in West Nusa Tenggara. The primary focus of this research is on non-compliance with international and domestic legal standards, including arrests without clear legal grounds, the use of torture, and detention without due judicial process. Changes in anti-terrorism regulations, as outlined in Law No. 5 of 2018 on the Eradication of Terrorism Crimes, raise concerns that arrest procedures may erode public trust in law enforcement agencies and affect social and economic impacts. This study finds that the lack of proper legal procedures and safeguards during the arrest of suspected terrorists often results in violations of both international human rights norms and domestic legal frameworks. The findings highlight the need to uphold human rights within law enforcement practices, alongside an urgent review of anti-terrorism regulations to prevent abuses. Strengthening accountability mechanisms is critical for restoring public trust and ensuring that counter-terrorism efforts do not compromise fundamental freedoms.